Evaluation of the Idhaf Lughawi Program at Islamic Boarding School Gontor For Gilrs 1 Using the CIPP Model - Ihwan Mahmudi; Siti Fadilah; Heru Saiful Anwar (Educan : Jurnal Pendidikan Islam, 2023)
This study aims to evaluate the implementation of the idhaf lughawi program at boarding school of  Darussalam Gontor Putri boarding school in terms of the following aspects: 1) Urgency (Context) 2) Source (Input) 3) Implementation (Program) 4) Outcome (Product). This study uses a qualitative approach and uses the CIPP Model to measure the level of achievement of programs or activities by the target group, or to measure the results of the implementation of context, inputs, programs and products (CIPP). The research design used is evaluative qualitative research and uses observation, interviews and documentation techniques. Based on the results of the study, it was shown that the overall Idhaf lughawi program held at Boarding School of  modern Darussalam Gontor Putri Islamic boarding school was categorized as good with the percentage of successful program achievements in detail, namely the context program 100%, Resources (Input) 90%, Implementation (Program) 88%, and results. (Product) 75%.